Myocardial Bridging Unmasks as an Acute Coronary Syndrome from Dehydration. (13th July 2021) - Maaliki, Naji; Omar, Michael; Ali, Aleem Azal; Roemer, Amy; Ruiz, Jose; Sadic, Edin
Abstract : A 50-year-old male presented for loss of consciousness. He was initially treated with intravenous epinephrine and fluids, and an electrocardiogram (ECG) displayed an ST-segment elevation in lead aVR with global ST-segment depressions. A subsequent left heart catheterization revealed that the middle segment of the left anterior descending artery (LAD) demonstrated severe stenosis during systole but would become patent during diastole, which was suggestive of myocardial bridging. After stopping the epinephrine and increasing the fluid infusion, the ECG changes rapidly resolved. The patient had later admitted to significant dehydration all day. Myocardial bridging is a congenital anomaly in which a coronary artery segment courses through the myocardium instead of the usual epicardial surface. Occasionally, myocardial bridging may present similarly to acute coronary syndrome in severe dehydration or hyperadrenergic states. The diagnosis can be made through coronary angiography, which reveals a dynamic vessel obstruction pattern corresponding with the cardiac cycle. Long-term effects may also include accelerated atherosclerosis. Treatment consists of reversing precipitating causes during acute presentations and decreasing the risk of coronary artery disease on a chronic basis.